Health Promotion for Stroke Patients at Grandmed Lubuk Pakam Hospital - Putri, Nindia; Tati Murni Karo-Karo (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2024)
Stroke is a major health problem for modern society today. Nowadays, stroke is increasingly becoming a serious problem faced almost all over the world. This is because a sudden stroke can result in death, physical and mental disability in both productive and elderly age. This research is to determine the role of health promotion on the motivation of stroke patients in receiving physiotherapy services at Grandmed Lubuk Pakam Hospital. This research is qualitative research which aims to explore a problem with detailed limitations, as well as collecting in-depth data. The number of informants in this study was 4 people. Data collection was carried out using an in-depth interview method equipped with a voice recording device with 4 informants. The principle of health promotion here is that the patient and the patient's family are able to understand or understand what is conveyed by the promotion officer which can then influence interest in doing or coming to health services. every patient or patient's family who is targeted can receive the promotion well. Grandmed Lubuk Pakam Hospital health promotion is emerging as a forum that leads or guides towards health prosperity for patients and their families. By emphasizing knowledge about the impact of stroke until post-stroke and how to function, the body can move freely as before. providing more interesting and creative methods or means so as to attract the attention and interest of patients and the patient's family to listen and understand more easily and more pleasantly.